Assessment of hepatitis C viral load and genotypes by molecular determination in Iraqi patients treated with Ledipasvir/sofosbuvir (Harvoni) drug - Hussein, Sahib A.; Al-azzawi, Raghad H.; Alshareef, Duraid Qassim (Iraqi Journal of Science, 2021)
Hepatitis C virus ( HCV) is a significant global health threat that is responsible for approximately 170 million chronic infections worldwide. A feasible research was conducted to provide more understanding of viral load, effectiveness of Harvoni drug on virus concentration, and distribution of virus genotypes in Iraqi patients. Ninety eight HCV cases were investigated in this research , including 52 untreated, with an average age ± SE of 45.26 ± 2.97 years, and 46 treated with Harvoni therapy, with an average age of 39.30 ± 3.90 years. In addition, eighty healthy persons with an average age of 29.40 ± 2.84 years were included as control. These cases were attending to the Special Nursing Home Hospital in Baghdad between December 2018 and January 2019. They were diagnosed with this disease by using a real-time PCR to concentrate the viral level and determine viral genotypes. Statistical analysis showed that high substantial variances in virus concentration between untreated and treated patients and between both groups versus apparently healthy volunteers group (p < 0.01). Furthermore, genotype 4 was shown to be higher in our sample of Iraqi hepatitis C patients in comparison with the other patterns.